2011
DOI: 10.1021/ie101959t
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Analysis and Hydrate Dissociation Conditions Measurements for Carbon Dioxide + Methane + Water System

Abstract: Publication Date (Web): March 24, 2011International audienceA detailed description of an experimental setup based on the "static-analytic" technique with gas phase capillary sampling designed, built, and improved "in-house" to measure phase equilibria (pressure, temperature, and compositions) under gas hydrate formation conditions is presented in this work. The apparatus is suitable for measurements at temperatures ranging from 233 to 373 K and pressures up to 60 MPa. It was used to study phase equilibria in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
89
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 33 publications
1
89
0
Order By: Relevance
“…Acosta et al found that, with CO 2 /CH 4 gas mixtures (0.4/0.6 and 0.6/0.4), the pressure required to form semi‐clathrates at a given temperature decreased as the TBAB concentration increased. Mohammadi et al measured and reported the clathrate/semi‐clathrate hydrate formation and dissociation conditions for systems containing CO 2 /CH 4 mixtures in the presence of pure water and different mass fractions of TBAB aqueous solutions. A significant decrease in the operating pressure was observed during gas hydrate formation for separation of CO 2 from the corresponding gas mixtures due to the hydrate promotion effects of TBAB.…”
Section: Introductionmentioning
confidence: 99%
“…Acosta et al found that, with CO 2 /CH 4 gas mixtures (0.4/0.6 and 0.6/0.4), the pressure required to form semi‐clathrates at a given temperature decreased as the TBAB concentration increased. Mohammadi et al measured and reported the clathrate/semi‐clathrate hydrate formation and dissociation conditions for systems containing CO 2 /CH 4 mixtures in the presence of pure water and different mass fractions of TBAB aqueous solutions. A significant decrease in the operating pressure was observed during gas hydrate formation for separation of CO 2 from the corresponding gas mixtures due to the hydrate promotion effects of TBAB.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the crystalline and thermodynamic properties can vary significantly from those of hydrate formed from pure gases based on the combination and ratio of hydrate formers . Thus, the phase equilibrium conditions of CO 2 /CH 4 gas mixture have been studied by many researchers . By employing the isobaric temperature search method, Seo et al acquired three‐phase equilibria data for the CO 2 ‐CH 4 ‐H 2 O system .…”
Section: Introductionmentioning
confidence: 99%
“…[1,16] Thus, the phase equilibrium conditions of CO 2 /CH 4 gas mixture have been studied by many researchers. [17][18][19][20][21][22][23] By employing the isobaric temperature search method, Seo et al acquired threephase equilibria data for the CO 2 -CH 4 -H 2 O system. [24] The solubility of methane and CO 2 under equilibrium conditions of hydrate, liquid water, and vapour was measured, and the effect of pressure on the equilibrium mole fraction of respective hydrate formers in the liquid was discussed by Bruusgaard et al [25] CO 2 /CH 4 gas mixture hydrate formation with and without THF were investigated by Lee et al, who found that the CH 4 /CO 2 (50:50) gas mixture hydrate formed the s-I hydrate, instead of the s-II hydrate formed by the THF þ CO 2 /CH 4 gas mixture.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrates have the potential for many industrial applications: flow assurance in petroleum industry [13][14][15][16], CO 2 capture and sequestration [17][18][19][20][21][22], separation of close-boiling point compounds [23][24][25], water desalination [26], gas (H 2 and CH 4 ) storage [27][28][29], refrigeration and cool storage [30][31][32].…”
Section: Introductionmentioning
confidence: 99%